1983
DOI: 10.5006/1.3580829
|View full text |Cite
|
Sign up to set email alerts
|

The Anodic Dissolution of a Ni-Base Superalloy

Abstract: A single phase nickel base superalloy, HASTELLOY Alloy C-276, was anodically polarized in 0.5 N NaCl at 70 C, and the concentrations of metal-ion complexes in solution were determined. Relative dissolution rates of alloying elements were obtained and selectivity coefficients were calculated. The corrosion products that formed at high anodic potentials were identified as FeCl2+, Ni2+, HCrO4−, and MoO42−. The pH was observed to decrease and the chloride ion concentration to increase in the electrolyte when diffu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0
1

Year Published

1984
1984
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 0 publications
2
10
0
1
Order By: Relevance
“…This was consistent with the observations of others that Mo-containing alloys exhibit lower crevice pH. 16,25 The dissolution and hydrolysis of Mo containing species is quite complex, depending upon the potential and acidity of the solution. For example, at high applied potentials, dissolution of Mo to form Mo(VI) results in the formation of molybdate (MoO 4 2-) and generation of H + by the following reaction: …”
Section: Effect Of Alloy Composition On Ph Changessupporting
confidence: 90%
See 2 more Smart Citations
“…This was consistent with the observations of others that Mo-containing alloys exhibit lower crevice pH. 16,25 The dissolution and hydrolysis of Mo containing species is quite complex, depending upon the potential and acidity of the solution. For example, at high applied potentials, dissolution of Mo to form Mo(VI) results in the formation of molybdate (MoO 4 2-) and generation of H + by the following reaction: …”
Section: Effect Of Alloy Composition On Ph Changessupporting
confidence: 90%
“…However, when Mo content in the alloy was very high, such as in alloy C-276 (UNS N10276, [1] 16% Mo), Mo concentration in the solution decreased, and the resulting pH in the pit was higher than a lower Mo-containing alloy, such as type 316L SS (UNS S31603). 25 The total Clconcentration increased to values as high as 12 N. However, there was a maximum in Clconcentration inside pits at intermediate values of pit volumes, corresponding to a pit diameter of ~ 0.4 mm. [16][17] The Clconcentration inside crevices, which usually can be regarded as large pits, has not been found to attain such large values.…”
Section: Corrosion-november 1994mentioning
confidence: 91%
See 1 more Smart Citation
“…i HCl = 3 × 10 −6 e 1.3·m HCl [12] where i HCl is the peak current density, and m is the HCl concentration in molal. Equating the HCl and metal salts relationships, i salt = i HCl , the following relationship is obtained …”
Section: Discussionmentioning
confidence: 99%
“…Cavanaugh et al 12 studied the composition of an alloy C-276 solution produced by a high anodic polarization (10 mA/cm 2 ). Analysis of the dissolved metal cations in solution indicated that the relative dissolution rates of the alloy elements were Fe≥Ni>Mo>Cr.…”
mentioning
confidence: 99%